An MPS-based particle method for simulation of multiphase flows characterized by high density ratios by incorporation of space potential particle concept. (1st September 2018) - Shimizu, Yuma; Gotoh, Hitoshi; Khayyer, Abbas
Abstract: Simulation of multiphase flows characterized by high density ratios is targeted by using a refined particle method. The proposed method is founded on Moving Particle Semi-implicit (MPS) method which is a projection-based particle method. The proposed method comprises of a decoupled two-step computational algorithm through application of a consistent scheme for coupling the light/heavy phases by incorporating the concept of Space Potential Particles (SPP). The proposed coupling scheme guarantees the continuity of pressure and space (volume conservation) at the phase interface without any need for commonly applied density smoothing/averaging schemes or application of numerical stabilizing terms. Verification of the proposed multiphase particle method is conducted through the simulations of four benchmark tests and the method is shown to possess acceptable accuracy and convergence properties. Highlights: A refined particle method is proposed for simulation of multiphase flows with high density ratios. A consistent coupling scheme is developed based on the concept of space potential particles. The coupling scheme guarantees the continuity of pressure and space at phase interface. The method preserves density discontinuity at the phase interface. The method is shown to have good accuracy and convergence property.